1995
DOI: 10.1083/jcb.130.6.1473
|View full text |Cite
|
Sign up to set email alerts
|

Heparin is an adhesive ligand for the leukocyte integrin Mac-1 (CD11b/CD1).

Abstract: Abstract. Previous studies have demonstrated that the leukocyte integrin Mac-1 adheres to several cell surface and soluble ligands including intercellular adhesion molecule-I, fibrinogen, iC3b, and factor X. However, experiments with Mac-l-expressing transfectants, purified Mac-l, and mAbs to Mac-1 indicate the existence of additional ligands. In this paper, we demonstrate a direct interaction between Mac-1 and heparan sulfate glycans. Heparin affinity resins immunoprecipitate Mac-l, and neutrophils and transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
201
3
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(209 citation statements)
references
References 73 publications
4
201
3
1
Order By: Relevance
“…Mac-1 (CD11b/CD18), a monocytic counter-receptor for ICAM-1 that also binds to heparin (12), is present on Mono Mac 6 but not U937 cells, and may thus explain these differences in adhesion (11). Consistently, oxLDL induces a two-fold upregulation of ICAM-1 but not vas-cular cell adhesion molecule (VCAM)-1 or E-selectin surface expression on HUVEC.…”
Section: Monocyte Adhesion To Oxidized Low Density Lipoprotein-stimulmentioning
confidence: 91%
See 1 more Smart Citation
“…Mac-1 (CD11b/CD18), a monocytic counter-receptor for ICAM-1 that also binds to heparin (12), is present on Mono Mac 6 but not U937 cells, and may thus explain these differences in adhesion (11). Consistently, oxLDL induces a two-fold upregulation of ICAM-1 but not vas-cular cell adhesion molecule (VCAM)-1 or E-selectin surface expression on HUVEC.…”
Section: Monocyte Adhesion To Oxidized Low Density Lipoprotein-stimulmentioning
confidence: 91%
“…Distinct endothelial ligands induced by mmLDL (8, 9) do not appear to be identical with such ligands (16), since they mediate U937 adhesion, which is not increased by oxLDL. An inhibition of monocyte adhesion with the soluble Mac-1 ligand heparin (12) indicates that cellular heparan sulfate proteoglycans are involved in monocyte adhesion to untreated HUVEC. While heparin alone has no effect, combining heparin with ICAM-1 mAbs significantly inhibits monocyte adhesion to oxLDL-stimulated HUVEC.…”
Section: Monocyte Adhesion To Oxidized Low Density Lipoprotein-stimulmentioning
confidence: 99%
“…Mac-1 has also been shown to bind directly to heparan sulphate [130]. Assays carried out under conditions of physiological flow showed that Mac-1-heparan sulphate binding is not sufficient to mediate neutrophil adhesion.…”
Section: Cell-cell Adhesionmentioning
confidence: 99%
“…Neutrophil binding to E-selectin-coated surfaces causes reversible tethering (rolling), but is not able to support firm adhesion (arrest) at physiological shear stresses. When E-selectin and heparan sulphate are co-adsorbed on to a substratum, both receptors are utilized, so that E-selectin-mediated rolling allows the binding of Mac-1 to heparan sulphate to occur, resulting in firm adhesion of neutrophils at physiological shear stresses [130].…”
Section: Cell-cell Adhesionmentioning
confidence: 99%
“…More than 30 protein and nonprotein molecules have been reported to bind this receptor (22). These ligands include ICAMs 1, 2, and 3 (23), fibrinogen (24), factor X (25), complement C3 fragment (26), urokinase plasminogen activator receptor (27), E-selectin (28), catalase, transferrin (29), and some nonprotein ligands such as LPS (30) and heparin (31), etc.…”
mentioning
confidence: 99%